1995
DOI: 10.1159/000262049
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Electrical Conductance Measurements in Evaluating the Marginal Integrity of Sealant Restorations

Abstract: The use of sealants and sealant restorations has increased considerably over the past 10 years, and with it increased the problem of detecting secondary caries and marginal (micro)leakage. It was the purpose of this study to investigate the validity of electrical conductance measurements (ECMs) in diagnosing marginal leakage into dentine of sealants and sealant restorations. Ninety extracted premolar teeth were divided into three groups. Initial ECMs, denoted ‘baseline ECMs’, were conducted in all three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…The results of studies using this type of device and comparing the electrical measurements with other diagnostic systems (e.g., visual inspection, bite-wing radiographs, fibre-optic transillumination) have been very encouraging [Rock and Kidd, 1988;Verdonschot et al, 1992;Lussi et al, 1995;Ricketts et al, 1995]. Recently, it was suggested that the fissure system could be covered with a conducting medium, resulting in a surface-specific measurement Verdonschot et al, 1995]. In clinical practice, this would reduce the time needed for examinations.…”
mentioning
confidence: 99%
“…The results of studies using this type of device and comparing the electrical measurements with other diagnostic systems (e.g., visual inspection, bite-wing radiographs, fibre-optic transillumination) have been very encouraging [Rock and Kidd, 1988;Verdonschot et al, 1992;Lussi et al, 1995;Ricketts et al, 1995]. Recently, it was suggested that the fissure system could be covered with a conducting medium, resulting in a surface-specific measurement Verdonschot et al, 1995]. In clinical practice, this would reduce the time needed for examinations.…”
mentioning
confidence: 99%
“…The critical area of 7 mm2 will be easily reached in occlusal surface measurements, particularly in molar teeth. In a previous study Verdonschot et al [1995] mea sured electrode areas on occlusal surfaces o f premolars and found a range of 5-15 mm2. In the present study the occlusal electrode area did not exceed 10 mm2 (range: 5.4-9.7 mm2).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, quantitative methods for detecting gap formation, such as an air pressure 22,23 and electrical [24][25][26] methods have been reported. In the air pressure method, air was delivered under pressure to the floor of the cavity of the restorative and the release of air bubbles from the margin of the submerged restorative were observed under a microscope.…”
Section: Introductionmentioning
confidence: 99%